2015
DOI: 10.1177/1550059415584704
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality of Auditory Mismatch Negativity in Depression and Its Dependence on Stimulus Intensity

Abstract: Mismatch negativity (MMN) is thought to reveal several abnormalities of cognitive functioning. Although depression often affects cognitive functioning, previous studies concerning MMN in depressed patients provided conflicting results. In recent reports, it has been suggested that depressed patients may show abnormal auditory response to regular auditory stimuli presented with at a relatively high intensity. We thus recorded acoustic MMN in 16 drug-free patients suffering from moderate depression and in 10 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…This aligns with our previous study, which applied the same stimulus conditions and found no differences in MMN between first-episode depressed, recurrent depressed and non-depressed young and middle-aged adults (Ruohonen and Astikainen, 2017). Previous studies have found inconsistent results for the modulation of MMN in depression; some have found attenuated MMN in depressed participants (Takei et al, 2009;Naismith et al, 2012;Qiao et al, 2013;Chen et al, 2015); some have found augmented MMN (Kähkönen et al, 2007;He et al, 2010;Restuccia et al, 2016); and some have found no difference in MMN between depressed and controls (Umbricht et al, 2003). The discrepancies among the studies could be related to differences in the applied stimuli or the type of deviance.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This aligns with our previous study, which applied the same stimulus conditions and found no differences in MMN between first-episode depressed, recurrent depressed and non-depressed young and middle-aged adults (Ruohonen and Astikainen, 2017). Previous studies have found inconsistent results for the modulation of MMN in depression; some have found attenuated MMN in depressed participants (Takei et al, 2009;Naismith et al, 2012;Qiao et al, 2013;Chen et al, 2015); some have found augmented MMN (Kähkönen et al, 2007;He et al, 2010;Restuccia et al, 2016); and some have found no difference in MMN between depressed and controls (Umbricht et al, 2003). The discrepancies among the studies could be related to differences in the applied stimuli or the type of deviance.…”
Section: Discussionsupporting
confidence: 90%
“…The discrepancies among the studies could be related to differences in the applied stimuli or the type of deviance. Studies that associated augmented MMN with depression applied frequency changes and relatively high stimulus intensities (Kähkönen et al, 2007;He et al, 2010;Restuccia et al, 2016); studies that associated attenuated MMN with depression mostly applied duration changes (Naismith et al, 2012;Qiao et al, 2013;Chen et al, 2015). Possibly, the intensity change condition (used in the present study) is not the best tool for detecting depression-related effects on the MMN time window.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations